Impact of the sewage discharge from hot springs to water sources (2021)
Hot springs have traditionally been a tourist attraction in many parts of the world, such as Japan, Canada, Taiwan among others. During the peak tourist season, it is usually discharged into streams without treatment, which can affect the quality of the receiving water, causing negative impacts to the aquatic ecosystems. Downstream ecological impacts of several major spa recreational sites in different parts of the world have been studied, and it has been found that wastewater discharges of hot springs have adverse ecological effects. The mineral composition in hot springs, derived mainly from groundwater, is usually greater than that of stream water. Studies carried out with models such as QUAL2K (or Q2K), the modernized version of the QUAL2E (or Q2E), simulate the effect of the hot spring discharges on surface water sources, mainly negative in nature. Despite the negative consequences of the impacts on ecosystems derived from hot springs’ wastewater, it is interesting to note that there are regulations for wastewater discharges – including backwash water from swimming pools – into rivers and sewers (e.g., Germany and Canada), but not specifically for hot springs discharge. Nonetheless, this evidence indicates a necessity for the authorities to increase the control of the use of hot springs and the discharge of their untreated waters. In Colombia, Resolution 631 of 2015 regulates the discharge of wastewater into rivers and sewers. Yet, it does not consider parameters for the discharge of hot springs. However, the authors deem it necessary to advance in the investigation on the contamination of the wastewaters coming from hot springs, and think about a sustainable tourism of hot springs.